"Are their voices being heard?" An exploration of female breast cancer communication in Kwa Zulu Natal, South Africa. Issue 7 (7th September 2021) - Zwane, Duduzile
Abstract: Breast cancer is a titanic health problem. It was once prevalent mainly in Developed countries. However, new cases are rapidly being diagnosed in the Developing world. In South Africa, it is the most common type of cancer amongst women. Further, Black women have a lower chance of surviving breast cancer than their White counterparts. This is partially due to economic and communication constraints. Consequently, in this article I explore the breast cancer communication strategy of a prominent hospital in Kwa Zulu Natal (KZN), South Africa. I conducted 30 semi-structured interviews with Black, Zulu women at this institution. My findings demonstrate that the hospital practices a banking style of communication, which encumbers the patients' capacity to acquire breast cancer information. Thus, I propose a participatory communication approach. This will equip the patients with vital knowledge which can be disseminated to their communities. Gradually, the threat of breast cancer can be conveyed throughout KZN.